ANALYSIS OF THE EFFECT OF SMART TOURISM TECHNOLOGY AND MEMORABLE TOURIST EXPERIENCE ON TOURIST LOYALTY WITH TOURIST SATISFACTION AS A MEDIATING VARIABLE - Are, Robert La (International Journal Multidisciplinary Science, 2024)
The involvement of innovative tourism technology in life, especially in tourism activities, plays a vital role in the process. Tourists use smart tourism technology devices to determine the destinations they want to visit. In line with this, tourists who utilize innovative tourism technology will have an impressive travel experience. All experiences tourists gain will later be expressed in images to immortalize their journey or positive comments or comments on innovative tourism technology media. These positive reviews indicate tourist satisfaction, where tourists get more results than expected. Tourists' satisfaction with innovative tourism technology and impressive experiences opens up opportunities for them to consistently use smart tourism technology devices and become more in-depth with information about areas they want to revisit or visit. This research aims to determine the influence of intelligent tourism technology and memorable tourism experiences on tourist loyalty, which is mediated by tourist satisfaction. This research uses a descriptive method with a quantitative approach through questionnaire instruments. The number of respondents used as data sources was 200 using the Probability Sample technique. This research uses Exploratory (Correlational Study), which aims to investigate a phenomenon that occurs or has yet to be explained well before. Data processing in this research used SEM PLS 4.0. The research results show that Smart Tourism Technology has yet to be proven to influence Tourist Satisfaction significantly. In contrast, a Memorable Tourism Experience is proven to influence Tourist Satisfaction significantly, and Tourist Satisfaction significantly influences Tourist Loyalty.